Use the elimination method to solve the system of equations.

x + y = 7

2x + y = 11

x + y = 7

2x + y = 11

x + y = 7

2x + y = 11

---------------

-x = -4 {subtracted the two equations, eliminating the y}

x = 4 {divided each side by -1}

x + y = 7 {top original equation}

4 + y = 7 {substituted 4, in for x, into top original equation}

y = 3 {subtracted 4 from each side}

(4,3) is the solution to the system of equation. This means the coordinates (4,3) are where the two lines intersect, when graphed, as shown below.

2x + y = 11

---------------

-x = -4 {subtracted the two equations, eliminating the y}

x = 4 {divided each side by -1}

x + y = 7 {top original equation}

4 + y = 7 {substituted 4, in for x, into top original equation}

y = 3 {subtracted 4 from each side}

**x = 4 and y = 3**(4,3) is the solution to the system of equation. This means the coordinates (4,3) are where the two lines intersect, when graphed, as shown below.

*- Algebra House*